PENGARUH UPAH MINIMUM PROVINSI DAN ANGKATAN KERJA TERHADAP TINGKAT PENGANGGURAN DI PROVINSI BANTEN TAHUN 2010-2023 - Wasi'aturohmah, Binti; Winanto, Asis Riat; Abas, Sayid (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.02.TAHUN.2025DO - 10.24843/EEB.2025.v14.i02.p01, 2025)
The aim of this study is to analyze the impact of the provincial minimum wage (UMP) and the size of the workforce on the unemployment rate in Banten Province in 2010-2023. As a regional economic policy, the UMP is considered to play an important role in influencing the unemployment rate, while the size of the workforce, which is a demographic variable, can also influence employment conditions. The data used in this study is in the form of secondary data using a quantitative approach and multiple linear regression. Data source from BPS Banten Province. The findings from the analysis show that the UMP partially has a negative effect on the unemployment rate, while the labor force partially has a positive effect on the unemployment rate. Simultaneously, both the UMP and the labor force have an influence on the unemployment rate in Banten Province. With the government programme above, it is hoped that it can reduce the labour force and minimise the unemployment rate in Banten Province, and with this it is hoped that Banten Province will no longer be the province with the highest unemployment rate in Java.